Implementation Model Learning Innovation of direct Learning in Social Sciences at Elementary School - Elfa , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The background of this research in an elementary school, a teacher lacking conveying learning objectives, lack of providing skills to students, lack of training, and lack of feedback to the student in the learning process social sciences. This problem affects the students are less active and creative, so the study results is below the average KKM (6) specified in the school. This study aimed to describe "How to student learning outcomes in social studies learning by using direct instructional model in class VI Elementary School No. 26 West Sikapak Barat Pariaman". This research is a classroom action research (PTK) using qualitative and quantitative approaches, and the research conducted in the first half year 2010/2011. As the subjects in this study were teachers and students of the sixth grade Elementary School No. 26 Sikapak Barat Pariaman which amounted to 15 people. This study consisted of two cycles, each cycle consisting of two meetings. Research procedures including planning, implementation, observation and reflection. The results showed observation of the lesson plan in the first cycle 78% with good qualifications and cycle II increased 93% with excellent qualifications. Conduct observations on aspects of teacher learning cycle I 70.08% with good qualifications, and the second cycle increased 80.80% with excellent qualifications. While the students in the first cycle aspects of 70.08% with good qualifications, on the second cycle increased to 80.80% with excellent qualifications. Student learning outcomes in the first cycle 72 with a good qualification and in cycle 2 increased to 83.2 with excellent qualifications. Thus the model estab direct learning can improve student learning outcomes in social studies learning in class VI SDN 21 Sikapak Barat District of North Pariaman